ASSESSING THE EFFECT OF KITCHEN LAYOUT ON EMPLOYEE’S PRODUCTIVITY - Hagan, Joana Adwoa; Kwofie, Adelaide Spio; Baissie, Faustina (IJRDO - Journal of Applied Management Science, 2017)
A cross sectional survey was conducted to assess the impact of kitchen layout on employees’ productivity. A purposive sampling technique was used to select 90 respondents from three (3) company kitchens in the Takoradi Metropolis of Ghana. The samples included all kitchen staff irrespective of their gender, age and position. Data was collected from these respondents using a structured questionnaire and collected data was analyzed using the SPSS software. It was found out that most of the respondents did not have much knowledge about the concept of kitchen layout designs. Though a few of the respondents reported that their kitchen layout makes work difficult, most indicated that the layout of the kitchen they work in makes their work very easy. Majority of them also indicated that their kitchen arrangements gave them enough space to operate which allowed them to have easy movement from one station to another thereby improved their working speed. Finally, only half of the respondents said they knew that working in a poor layout designed kitchens could have some effects such as stress, respiratory problems, bodily pains and headaches on their health. The study recommends that kitchen staff be educated on the concept of their kitchen layout and the associated benefits to boost productivity.